Strategy Implementation as a Middle Manager: Maintaining and Disrupting Institutions Simultaneously - Hand, Graeme Carrick (Auckland University of Technology, 2022)
Strategy is often seen as an activity undertaken by senior managers. Often overlooked is the impact strategic change has on the customer facing team managers. This study focuses on strategic implementation activities by team managers in the New Zealand telecommunications industry and reviews their lived experiences through the theoretical lens of institutional work, a theory which takes an institutional view of activities that create, maintain, and disrupt institutions. Participants were interviewed about implementation activities and findings developed using a qualitative interpretative approach. Institutional work is found to be performed at all three categories simultaneously by managers. A conceptual model is provided that contrasts the interaction of organisational complexity against institutional work classes of Adaptation, Translation, Orientation, and Integration.